Analisis Pengaruh Konflik Rumah Tangga, Pengangguran dan Kemiskinan Terhadap Angka Perceraian di Jawa Barat Tahun 2020-2024 - Rabbani, Ahmad Fakhri; Muhammad Farid Al-Hafizh; M. Shadam Naswa Siamutiq; Muhammad Najib Nurkhadziqi; Ahmad Fauzan; Dimas Kristian; Suraya Murcitaningrum (Journal of Macroeconomics and Social Development, 2025)
Research explores the impact of domestic conflict, unemployment, and poverty on divorce rates in West Java Province between 2020 and 2024. The core objective is to determine which socio-economic factors most significantly contribute to the increase in divorce cases, as well as to assess the relative influence of each variable on this trend. A quantitative methodology was employed, utilizing panel data regression through the Random Effect Model (REM). The dataset comprises information from 26 districts and cities in West Java over a five-year period, with analysis conducted using EViews 10 software and primary data sourced from the West Java Bureau of Statistics (BPS). The study’s findings indicate that domestic conflict and poverty have a significant positive correlation with divorce rates, meaning that as levels of conflict and economic hardship rise, so does the likelihood of divorce. Interestingly, unemployment displays a significant negative relationship with divorce, possibly due to financial limitations that discourage couples from pursuing legal separation. The regression model explains approximately 42.32% of the variance in divorce rates, suggesting that other unexamined factors also play a role. These insights emphasize the need for strategic social and economic interventions aimed at bolstering family stability and curbing divorce in the region